2014
DOI: 10.3109/09537104.2013.865835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a new platelet count drop method PL-11, light transmission aggregometry, VerifyNow aspirin system and thromboelastography for monitoring short-term aspirin effects in healthy individuals

Abstract: Platelet function has been described by many laboratory assays, and PL-11 is a new point-of-care platelet function analyzer based on platelet count drop method, which counts platelet before and after the addition of agonists in the citrated whole blood samples. The present study sought to compare PL-11 with other three major more established assays, light transmission aggregometry (LTA), VerifyNow™ aspirin system and thromboelastography (TEG), for monitoring the short-term aspirin responses in healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In the one hand, thrombin generation was directly measured via newly developed calibrated automated thrombogram method rather than indirectly evaluated by thrombin-antithrombin complex and prothrombin fragment 1 þ 2 [17]. On the other hand, the modified automated impedance technique based on the whole blood simplified the detecting process of PAg and time-saved [11]. Additionally, unlike previous study [14], about 4 min initial delay of TF-induced PAg was observed in novel anticoagulants pretreated whole blood, which was consistent with the Lagtime in plasmatic thrombin generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the one hand, thrombin generation was directly measured via newly developed calibrated automated thrombogram method rather than indirectly evaluated by thrombin-antithrombin complex and prothrombin fragment 1 þ 2 [17]. On the other hand, the modified automated impedance technique based on the whole blood simplified the detecting process of PAg and time-saved [11]. Additionally, unlike previous study [14], about 4 min initial delay of TF-induced PAg was observed in novel anticoagulants pretreated whole blood, which was consistent with the Lagtime in plasmatic thrombin generation.…”
Section: Discussionmentioning
confidence: 99%
“…PAg was evaluated by a kinetic counting method via PL-11 platelet analyzer (SINNOWA, Nanjing, China) based on an automated impedance technique [11]. In brief, a 288-ml citrated blood sample was transferred into a polycarbonate tube, mixed with 12 ml of increasing concentrations of dabigatran, rivaroxaban or vehicles, and incubated at 378C for 5 min.…”
Section: Platelet Aggregation Testmentioning
confidence: 99%
“…Therefore, platelet function assays were not equally interchangeable and the correlations among them were varied. PL-11 by “sequentially platelet counting method” gives more exact and stable results of platelet counting before and after the addition of agonists in the citrated whole blood samples, which has been demonstrated to be correlated with LTA and VerifyNow [11]. Consequently, sequentially platelet counting method by PL-11 would bean optional device for platelet function tests.…”
Section: Discussionmentioning
confidence: 99%
“…PL-11 analyzer (SINNOWA Co., Nanjing, China) was used for the test [11, 12]. With standardized and easier test method, the analyzer gives more exact and stable results of platelet maximum aggregation ratio (MAR%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation